PENYEMBUHAN DALAM PENEBUSAN KISTUS MENURUT YESAYA 53: 4 – 6 - Cahyono Budi Wibowo (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
Some of Charismatic ministers tend to give it equal weight and emphasis, arguing from experience. Their books are often filled with claims of healings and deliverances that have occurred, but there is also evidence that these claims are invalid and healings are questionable. There are also those who seem to be healed after prayer but after returning home they become sick again, so healing here is just a suggestion. Therefore, all experiences must be subject to the authority of Scripture, as the Apostle Peter said in comparing the Scriptures with his experience of the transfiguration of Christ: “Knowing this first, that no prophecy of the scripture is of any private interpretation” (2Pet. 1:20). This paper was written using a qualitative method and in the study of literature departs with the assumption that the Bible has its own meaning which is in accordance with texts about healing. The purpose of this paper is to examine the concept of the meaning of healing in the atonement of Jesus Christ through an exegetical study of Isaiah 53:4-6, which clearly implies that by His stripes we are healed referring to eschatology.